The UN convention on the rights of the child, decentralisation and legislative integration: a case study from Wales. Issue 3 (16th March 2019) - Hoffman, Simon
ABSTRACT: Despite decentralisation being a ubiquitous feature of human rights governance globally, the UN Committee on the Rights of the Child focuses primarily on the State as the locus for implementation of the UN Convention on the Rights of the Child (CRC). State control and a regulative approach prioritising justiciability of the CRC at national level are the Committee's dominant responses to decentralisation. This paper introduces decentralisation, including the risks and potential gains for CRC implementation. It is contended that a regulative approach may prove particularly challenging in the context of decentralisation. It is suggested that a normative approach, in which legislation is used to promote compliance through cultural acceptance of the CRC, and to support localisation of rights, may be better suited to the contours of decentralised governance. Taking the example of Wales, a devolved territory in the United Kingdom, it will be shown how a primarily normative approach to legal integration can help mainstream international norms in policy, enhance accountability for rights, and provide opportunities for policy advocacy at local level. The paper is a contribution to the literature on the instrumental value of legislation to support the realisation of human rights, applicable to decentralised systems of governance.